METHODOLOGY FOR ASSESSING THE EXPORT POTENTIAL OF REGIONAL EDUCATION SERVICES (International journal of artificial intelligence, 2025)
This article examines the scientific and methodological foundations for assessing the export potential of regional education services, with an emphasis on empirical and statistical justification. In the context of the global knowledge economy, education services have become a significant component of international trade, generating substantial economic returns for host countries and regions. According to international analytical estimates, the global market for international education services exceeds USD 250 billion annually, while the number of internationally mobile students worldwide has surpassed 6 million, compared to less than 2 million at the beginning of the 2000s. Against this background, the identification and evaluation of regional education export capacity becomes increasingly important. The study proposes a comprehensive methodological approach that integrates quantitative and qualitative indicators, including educational infrastructure, academic quality, institutional environment, international cooperation, and digital education development. The article demonstrates how assessment results can support evidence-based regional education policy and strategic planning.